PENGARUH KEPEMIMPINAN, LOYALITAS KARYAWAN DAN KINERJA KARYAWAN TERHADAP KUALITAS PELAYANAN UNIT LAYANAN PENGADAAN BARANG/JASA - Ernawati, Mamik Subagyo, Djoko Suseno & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2016)
This research is conducted to know the significancy betwen (1) leadership (2) of employee loyalty (3) the performance of employees on the quality services of The Unit Layanan Pengadaan Barang dan Jasa Kabupaten Ngawi.The population is all employees who work in The Unit Layanan Pengadaan Barang dan Jasa Kabupaten Ngawi as many as 32 employees. The analysis Technique usesdouble regression analysis with the classical assumption. Analysis results showed that leadership, employee loyalty and employee performance has positive and significant effect on service in The Unit Layanan Pengadaan Barang dan Jasa Kabupaten Ngawi. The most dominant variable effect on the quality of service is the employee's performance because this variables has the greatest coefficient is 0, 689. Leadership, employee loyalty and employee performance positive effect on office services The Unit Layanan Pengadaan Kabupaten Ngawi was 82,4%.Keywords: leadership, loyalty, employee performance, quality of service